Achieving low dielectric, surface free energy and UV shielding green nanocomposites via reinforcing bio-silica aerogel with polybenzoxazine. (23rd May 2017) - Prabunathan, P.; Thennarasu, P.; Song, J. K.; Alagar, M.
Abstract : Silica aerogel (SA) derived from rice husk ash was functionalized using benzoxazine terminated silane (FSA) and was used as a nanoreinforcement for industrial valuable resin polybenzoxazine (PBZ) in order to achieve low dielectric, to improve the surface as hydrophobic and to enhance the UV shielding behavior of the resulting nanocomposites. Abstract : In the present study, silica aerogel (SA) derived from rice husk ash was functionalized using benzoxazine terminated silane (FSA) and was used as a nanoreinforcement for industrial valuable resin polybenzoxazine (PBZ) in order to improve the dielectric, surface and UV shielding behavior of the resulting nanocomposites. From the data of different studies, it was observed that the porous morphology, lower polarity due to the presence of a siloxane network and hydrophobic nature of FSA contribute to both the low dielectric constant (2.16) and low surface free energy (mJ m −2 ) with a high shielding behavior of 94.4%. Thus, the green nanocomposites obtained from ecofriendly biomass silica with a low dielectric constant, low surface free energy and high UV shielding behavior can be used as adhesives, sealants and encapsulants for high performance microelectronics insulation applications, where structural integrity is warranted.